'Localising' humanitarian action: reflections on delivering women's rights-based and feminist services in an ongoing crisis. Issue 2 (4th May 2019) - Al-Abdeh, Maria; Patel, Champa
ABSTRACT: This article shares the experiences of Women Now for Development, a women's organisation working with Syrian women in Syria and neighbouring countries. The key questions under consideration are whether important policy commitments to empower local actors are bearing fruit in practice and identify some of the challenges that still frustrate working with women and girls in humanitarian settings. This article aims to consider whether localisation is more than a current 'buzz-word'.